Transcriptional signature of early cisplatin drug-tolerant persister cells in lung adenocarcinoma - Chavez-Dominguez, Rodolfo; Aguilar-Cazares, Dolores; Perez-Medina, Mario; Avila-Rios, Santiago; Soto-Nava, Maribel; Mendez-Tenorio, Alfonso; Islas-Vazquez, Lorenzo; Benito-Lopez, Jesus J.; Galicia-Velasco, Miriam; Lopez-Gonzalez, Jose S. (Frontiers in Oncology, 2023)
Resistance to cisplatin is the main cause of treatment failure in lung adenocarcinoma. Drug-tolerantpersister (DTP) cells are responsible for intrinsic resistance, since they survive the initial cycles of treatment, representing a reservoir for the emergence of clones that display acquired resistance. Although the molecular mechanisms of DTP cells have been described, few studies have investigated the earliest molecular alterations of DTP cells in intrinsic resistance to cisplatin. In this work, we report a gene expression signature associated with the emergence of cisplatin-DTP cells in lung adenocarcinoma cell lines. After a single exposure to cisplatin, we sequenced the transcriptome of cisplatin-DTPs to identify differentially expressed genes. Bioinformatic analysis revealed that early cisplatin-DTP cells deregulate metabolic and proliferative pathways to survive the drug insult. Interaction network analysis identified three highly connected sub-modules in which SOCS1 had a significant participation in controlling the proliferation of cisplatin-DTP cells. Expression of the candidate genes and their corresponding protein was validated in lung adenocarcinoma cell lines. Importantly, the expression level of SOCS1 was different between CDDP-susceptible and CDDPresistant lung adenocarcinoma cell lines. Moreover, knockdown of SOCS1 in the CDDP-resistant cell This is a provisional file, not the final typeset article line partially promoted its susceptibility to CDDP. Finally, the clinical relevance of the candidate genes was analyzed in silico, according to the overall survival of cisplatin-treated patients from The Cancer Genome Atlas. Survival analysis showed that downregulation or upregulation of the selected genes was associated with overall survival. The results obtained indicate that these genes could be employed as predictive biomarkers or potential targets to improve the effectiveness of CDDP treatment in lung cancer patients.